Block copolymer template-directed catalytic systems: Recent progress and perspectives - Kumar, Labeesh; Singh, Sajan; Horechyy, Andriy; Fery, Andreas; Nandan, Bhanu (Membranes, 2021)
Fabrication of block copolymer (BCP) template-assisted nano-catalysts has been a subject of immense interest in the field of catalysis and polymer chemistry for more than two decades now. Different methods, such as colloidal route, on-substrate methods, bulk self-assembly approaches, combined approaches, and many others have been used to prepare such nano-catalysts. The present review focuses on the advances made in this direction using diblock, triblock, and other types of BCP self-assembled structures. It will be shown how interestingly, researchers have exploited the features of tunable periodicity, domain orientation, and degree of lateral orders of self-assembled BCPs by using fundamental approaches, as well as using different combinations of simple methods to fabricate efficient catalysts. These approaches allow for fabricating catalysts that are used for the growth of single-and multi-walled carbon nanotubes (CNTs) on the substrate, size-dependent electrooxidation of the carbon mono oxide, cracking of 1,3,5-triisopropylbenzene (TIPB), methanol oxidation, formic acid oxidation, and for catalytic degradation of dyes and water pollutants, etc. The focus will also be on how efficient and ease-of-use catalysts can be fabricated using different BCP templates, and how these have contributed to the fabrication of different nano-catalysts, such as nanoparticle array catalysts, strawberry and Janus-like nanoparticles catalysts, mesoporous nanoparticles and film catalysts, gyroid-based bicontinuous catalysts, and hollow fiber membrane catalysts.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Block copolymer; Core-shell; Micelles; Nano-catalyst; Self-assembly; Yolk-shell